Perilaku Kepemimpinan, Promosi Jabatan, dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan - Cyntia Cokro; Cindy Tifani; Bagus Bagus; Jocelyn Tania; Felix Felix (IPM2KPE, 2022)
This research aims to examine and analyze the influence of leadership behavior, promotion, and physical work environment on the performance of employees of PT. Pawnshop (Persero) Medan. This research method is descriptive quantitative. Population and research sample using saturated sampling technique. Data analysis techniques start from data compilation, data tabulation to the testing stage. The statistical method used is multiple linear regression analysis. The results showed that 89.3% of employee performance can be explained by independent variables and the remaining 10.7% is explained by other factors that have not been considered in this regression. In conclusion, simultaneously and partially leadership behavior, promotion, and physical work environment have a significant effect on the performance of employees of PT. Pawnshop (Persero) Medan. Keywords:Employee Performance, Physical Work Environment, Leadership Behavior, Promotion